RITUAL PENGOBATAN BEDEKEH MASYARAKAT SUKU AKIT HATAS DI DESA TITI AKAR KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Normayulis Normayulis; Isjoni Isjoni; Ahmal Ahmal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: One of the tribes in Riau Province is the Akit Tribe. The Akit tribe is a tribe that inhabits North Rupat Island. One of the tribal traditions of the Akit tribe is a healing ritual called Bedekeh. Bedekeh is a sacred healing ritual where the Akit tribe still believes that all human diseases are caused by disturbance by spirits. The objectives of this study are 1) to know the origin of the Bedekeh treatment ritual, 2) to know how the process of the Bedekeh treatment ritual, 3) to know how the sick people perceive the Bedekeh treatment ritual, 4) to know how the sick tribal community perceives medical treatment. This study uses qualitative methods with data collection techniques in the form of observation, interviews and documentation. The results of this study indicate that 1) bedekeh ritual has existed since the time of their ancestors and has been passed down from generation to generation. 2) The process of implementing the bedekeh of the Akit Hatas tribe in Titi Akar Village, the first is the preparation stage before the bedekeh ritual, the second is the bedekeh ritual, the third stage is after the bedekeh ritual. 3) The Akit Hatas community's perception of bedekeh treatment still maintains the ritual because they consider it a legacy from the ancestors. 4) The perception of the Akit Hatas community towards medical treatment is quite helpful and some are of the view that medical treatment has side effects because it uses unnatural chemicals.Key Words: Treatment Ritual, Bedekeh, Akit Hatas Tribe, Titi Akar Village.